FIES: política pública de acesso e permanência no ensino superior - Barros, Michel Wanderson Oliveira de (2014)
The Brasil, despite having historical aspects, specific demands, characteristics regarding access and permanence in courses at private higher education institutions, is influenced by the principles, guidelines and actions outlined by the United Nations Educational, Scientific and cultural Organization (UNESCO) and the World Bank to develop the public, relating to higher education policy. Among the public policies developed by the government for higher education, three deserve special mention, as they contribute directly to the access and retention of students in higher education; they are: Fund Student Financing of Higher Education (FIES), the University for All Program (ProUni) and National Student Assistance Program (PNAES). This study aims to analyze how these policies, in particular the FIES, allow access and permanence of students in higher courses offered by the Faculdade Cearense. To encourage greater reflection on the subject, the Field Survey, which consists in observing the facts as they occur spontaneously in data collection and recording variables presumably was used for further analysis. The research as to the procedures, it is classified as descriptive, and may also be defined as the technical procedures used, bibliographic and documentary. The nature of the variables to be surveyed, the study is characterized by a qualitative and quantitative approach. The study will methodological approach, initially, the period 2010.1 to 2013.2, while in the Faculdade Cearense offers the student finance in total cover the tuition of students benefited. The observation occurs as access and permanence of students enrolled offered subsidies that enriched the analysis of the question, especially to understand how the subjects using the FIES to enter and remain in higher education.